Ocular manifestation of giant cell arteritis vs AL-amyloidosis: similar presentations but different approaches. (2nd January 2021) - Azarfar, Azin; Sharma, Aman; Parikh, Jignesh G.; Shaikh, Naazli M.; King-Morris, Kelli
Abstract: Light chain (AL) amyloidosis may present with the features of vasculitis, including giant cell arteritis (GCA). Similarities between GCA and AL-amyloidosis can potentially cause confusion in diagnosis, in which case, temporal artery biopsy (TAB) should be performed to make a definitive diagnosis. Herein we report a case of a bilateral anterior ischaemic optic neuropathy (AION), showing evidence of AL-amyloidosis on the temporal artery biopsy. A 75-year-old male with AL-amyloidosis secondary to monoclonal gammopathy of undetermined significance (MGUS) presented to our hospital for subacute painless progressive visual impairment. Based on his elevated inflammatory markers and his age, he was suspected to have giant cell arteritis. However, a temporal artery biopsy excluded GCA, and the Congo red staining was positive for amyloid deposition. This present case reveals that AL-amyloidosis may present with visual impairment, high inflammatory markers, and involvement of temporal arteries, concerning for GCA. TAB with Congo red staining is found to be crucial for making the correct diagnosis.